Continuous Learning for Employee Capacity Developing in Personal Mastery at Bank Indonesia - Iffah Budiningsih; Tjiptogoro Dinarjo Soehari; Eko Supriyanto (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this research is to discover the impact of continuous learning through strengthening competence, and innovation literacy on the improvement of performance. The research method used is a quantitative explorative technique with surveys with respondents being employees of the money management department at Bank Indonesia. The study samples are 160 out of the 272 total population, which were selected using simple random sampling. The data collection process was employed using a questionnaire. Subsequently, the data analysis process used descriptive statistical analysis and multiple regression, and before the regression analysis, requirement analysis was conducted using tests of normality, heteroscedasticity, autocorrelation & multicollinearity. The findings in this study are: a) competence and innovation literacy affect the level of achievement of employee performance in Institution X; b) the correlation between competence and innovation literacy on the performance of Institution X employees shows ‘positive’ and ‘strong’; c) competence and innovation literacy contribute to the achievement of Institution X’s employee performance by 52.8%, and the remaining 47.2% by other factors; d) innovation literacy has a higher level of sensitivity in achieving Institution X employee performance compared to competence; e) the results of this study imply the need to strengthen competence and innovation literacy through a decent & effective continuous learning in organizational, and the learning model of Technological Pedagogical Content Knowledge (TPCK) can be used as a continuous learning model in organizations/Institutions.